When plastic packaging should be preferred: Life cycle analysis of packages for fruit and vegetable distribution in the Spanish peninsular market - Abejón, R.; Bala, A.; Vázquez-Rowe, I.; Aldaco, R.; Fullana–i–Palmer, P. (Elsevier, 2020)
Food packaging is an important industrial sector that has great influence on food loss and waste. The search of optimal conditions to minimize the negative impacts of food packaging on the environment must promote the selection of the best available packages. This work has evaluated the environmental impact of the distribution of fruit and vegetables in the Spanish peninsular context using reusable plastic crates and single-use cardboard boxes. Discussion and decision at each phase and step of the methodology were provided, being an example to follow for similar studies in the future. For the analysis, five different impact categories were considered: global warming potential, acidification potential, eutrophication potential, ozone depletion potential and photochemical oxidant creation potential. In addition, energy and water consumption were taken into account. According to the results of the analysis, the use of reusable plastic crates should be selected, since the values of all impact categories and energy consumption indicators were higher in the case of single-use cardboard boxes. The sensitivity analysis revealed a robust preference for plastic crates in comparison with cardboard boxes even in alternative scenarios, and only the hypothetic reduction of the quality of the cardboard resulted in significant lower impacts for cardboard boxes in comparison to plastic crates in photochemical oxidant creation potential, acidification potential, and energy consumption. This work demonstrates that plastic packaging should not be totally excluded or banned, since it can be the most environmentally friendly option in certain applications.
Keywords: Food packaging; Environmental impact; Life cycle analysis; https://purl.org/pe-repo/ocde/ford#2.11.06